Literature review : Conditional based maintenance in manufacture industry - Koerniawan, Yani; Wahyu, Andhika (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Manufacturing companies are increasingly dependent on the performance of their equipment to remain competitive. The best performance equipment demands accurate and timely maintenance. ConditionBased Maintenance (CBM) is a strategy to prevent functional failures or a significant performance decrease of the monitored equipment. CBM which relies on a wide range of resources and techniques required to detect abnormal situations or predict the future condition of an asset. This paper will create framework to be a basic of guidlenes for selecting parameters. And emphasize framework with literature reviews. Then develop guidelines based on framework which emphasized by literature review. Finally, examine the guidelines by case studies to evaluate the effectiveness of proposed guidelines